Tax Evasion and Tax Avoidance: Effects on the Internal Revenue - Kaur, Gurpreet; Aanchal, (Gyan Management Journal, 2019)
Tax is that part of an individual's total income which helps the government to increase their revenue.  This amount is being utilized by the government for the purpose of development of the country such as  for the purpose of construction of buildings, roads etc. But, it has been found that the country has to face  various problems through tax evasion and avoidance. The aim of the study is to identify the reasons and  effects of tax evasion and tax avoidance. This study has used the secondary data from the annual  reports, from magazines etc. The findings of the study showed the amount of actual revenue collected  by the government have had a huge difference than the revenue expected by the government. The  reason behind this is tax evasion and avoidance. It has been conclude in this study that that these two  affects  the  internal  economy  badly.  The  revenue  of  government  gets  decreased  due  to  which  government  is  not  able  to  take  positive  measures  for  the  benefits  of  the  country.  It  has  been  recommended that if the amount of taxes will decrease, the problem can be reduced to a great extent.
Keywords: Hospitals; Service quality; SERVQUAL; Healthcare